Improving the Storability of Banana (Kuay Nam) by Using Gas Ozone: https://doi.org/10.69692/SUJMRD080236 - SIBOUNNAVONG, Phonesavard; XOUMPHONPHAKDY, Phanmaha; SENGSOURIYA, Phoudthavong; PHETSOMPHOU, Phonsine; DOUANDALA, Oudonexay; SAKBOUAVONG, Noumay; SIBOUNNAVONG, Phoutthasone (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This study is Improving the storability of banana by using quantity of gas ozone were to study quantity of ozone the physical characteristics and chemical changes and to acceptance of physiological in prolonging storage life of (Kuay Nam) banana and the experimental design using in CRD with 5 treatments as control, gas ozone 5 min, gas ozone 10 min, gas ozone 15 min and gas ozone 20 min, the results showed that banana was percent weight loss increasing by storage life in control percent weight loss more than the treatment were used ozone as 37.07%, for the value L*, a* and b* in control was change from green to yellow faster that other treatments, the total soluble solids (TSS), titrated acidity (TA) of banana were increasing by storage life. For the acceptance of physiological founded that the treatments using ozone gave the highest score more than control, because in control has wound and disease in surface peel of banana.